2017
DOI: 10.1007/s10388-017-0592-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of etilefrine regimen for chylothorax after esophagectomy with thoracic duct resection

Abstract: BackgroundManagement of postoperative chylothorax generally involves nutritional regimens as well as pharmacological and surgical therapies, but a clear consensus has yet to be reached.MethodsRetrospective review of 371 patients who underwent esophagectomy for esophageal cancer was performed. They were patients with squamous cell carcinoma or adenocarcinoma of the esophagus including Siewert type I/II tumor of the esophagogastric junction who underwent subtotal esophagectomy. Of these patients, 19 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Etilefrine acts by contracting the smooth muscle of the main lymphatic duct. In one of the biggest studies, a combination of etilefrine and octreotide showed an effectiveness of 75% [19,34,35]. If conservative measures fail, surgery should be performed (laparotomy or laparoscopy suture or clips ligation of the damaged lymphatic vessel).…”
Section: Discussionmentioning
confidence: 99%
“…Etilefrine acts by contracting the smooth muscle of the main lymphatic duct. In one of the biggest studies, a combination of etilefrine and octreotide showed an effectiveness of 75% [19,34,35]. If conservative measures fail, surgery should be performed (laparotomy or laparoscopy suture or clips ligation of the damaged lymphatic vessel).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, etilefrine is relatively safe because it rarely causes side effects such as headache, tachycardia, hypertension, and anxiety when used in proper dose. Ohkura et al [15] reported that the findings of their study suggest the effectiveness of etilefrine in patients with chylothorax following esophagectomy. Etilefrin (120 mg/day) was effective even in post-thoracic duct resection chylothorax, an often intractable condition that is difficult to treat conservatively.…”
Section: Etilefrinmentioning
confidence: 93%
“…Etilefrine , a sympathomimetic drug that causes contraction of smooth muscle fibers in the thoracic duct has been used, in combination with octreotide or not, in adult and neonatal patients with postoperative chylothorax 51–54 . Although experience with etilefrine is limited, it can be a novel option in the conservative treatment of neonatal chylothorax.…”
Section: Methodsmentioning
confidence: 99%